Aspek Hukum Pertimbangan Mahkamah Agung Mengabulkan Permohonan Kasasi Penuntut Umum dalam Perkara Narkotika - Jati Panuntun (Sebelas Maret University, 2019)
This study aims to determine the legal aspects of the Supreme Court’s consideration to grant the request of the Public Prosecutor in the narcotics case. The research method used is normative legal research. The approach used is the approach of law and case approach. Sources of legal materials used are primary and secondary legal materials. It is known that the Supreme Court’s consideration to grant the request of the Cassation of the Public Prosecutor stated that the Defendant commits a narcotic crime in accordance with the provisions of Article 256 jo of Article 193 paragraph (1) of the Indonesian Criminal Procedure Code where the Supreme Court declares that Judex Factie of the High Court of Surabaya has been wrong Applying the law therefore the Supreme Court adjudicates the case and declares that the Defendants are legally and convincingly proven guilty of committing a narcotic crime and sentence of imprisonment to Defendant I and Defendant II with imprisonment respectively for 4 (four) years And a fne of Rp.800.000.000,00 (eight hundred million rupiahs), respectively, provided that such fne is not paid, it shall be replaced by imprisonment for 1 (one) month.Keywords: Cassation, Legal Considerations, Narcotics Crime